Scaling Up Housing First Pilots – Drivers and Barriers - Marcus Knutagård; Arne Kristiansen (Nordic Journal of Social Research)
There has been an increased interest in Housing First services in Sweden over the past few years. The model was first developed in New York by the organization Pathways to Housing. The growing interest in Housing First as a response to ending long-term homelessness is seen not only in the US and Canada, but also in Europe. One reason for this is the mass of evidence showing high housing retention rates with Housing First services as compared with traditional services. This article aims to analyse the drivers and barriers that hinder or facilitate the scaling up of Housing First pilots. The research question is: Is it possible to incorporate lessons learned from the Housing First pilot into the existing system of homelessness services? In other words: Is it possible to put new wine into old bottles?